Impact of sustained health policy and population-level interventions on reducing the prevalence of obesity in the Caribbean region: A qualitative study from The Bahamas - Poitier, Francis; Kalliecharan, Ricky; Ebenso, Bassey (Frontiers in Public Health, 2022)
Background: The 2020 Global Nutrition Report highlights that despite improvements in select nutrition indicators, progress is too slow to meet the 2025 Global Nutrition Targets. While the Latin America and the Caribbean (LAC) region has achieved the greatest global reduction in undernutrition (stunting, underweight, and wasting) in the past decade, it also has the highest prevalence of people with overweight worldwide. Since the early 2000s, the region has mounted increasingly comprehensive and multi-sectoral policy interventions to address nutritional health outcomes. The Bahamas is one such LAC country that has used consistent policy responses to address evolving nutritional challenges in its population. After addressing the initial problems of undernutrition in the 1970s and 80s, however, overconsumption of unhealthy foods has led to a rising prevalence of obesity which the Bahamas has grappled with since the early 2000s. Objective: This study develops a timeline of obesity-related health policy responses, and explores the macrosocial factors and conditions which facilitated or constrained public health policy responses to obesity in The Bahamas over a 20-year period. Methods: This multi-method case study was conducted between 2019 and 2021. A document review of health policies was combined with secondary analysis of a range of other documents, and semi-structured interviews with key actors (policymakers, health workers, scholars and members of the public). Data sources for secondary data analysis included policy documents, national survey data on obesity, national and regional newspaper websites, and the Digital Library of the Caribbean database. An adapted framework approach was used for the analysis of semi-structured interviews. Results: Between 2000–2019, a series of national policies and community-level interventions were enacted to address the prevalence of obesity. Building on previous interventions, obtaining multisectoral collaboration, and community buy-in for policy action contributed to reducing obesity prevalence from 49.2% to 43.7% between 2012 and 2019. There are, however, constraining factors, such as political and multisectoral challenges, and gaps in legislative mandates and financing. Conclusion: Sustained multilevel interventions are effective in addressing the prevalence of obesity. To maintain progress, there is a need to implement gender-specific responses while ensuring accessibility, availability, and affordability of nutritious food for all.